Perancangan Interior Café Game di Surabaya - Ryan Daniel Santoso (Intra, 2019)
Internet cafes in Surabaya are designed only to play and lack a gathering place. There are many internet cafe designs in Surabaya that are economically designed because the target visitors are children and teenager and this have resulted in the fact that existing cafe designs are not attractive and have no themes. From these problems a Game Cafe is created with facilities for gathering and playing. To help gamers gather and socialize with other gamers, the design based on game themes could make gamers comfortable. The method used for the design process is design thinking, starting with understanding, observing, point of view, ideate, prototype, test and implementation. A gamer cafe design with themes from games can help attract young people. In terms of color, space organization, and furniture forms, they articulate two different sides according to the concept of online game play.